2019
DOI: 10.1002/14651858.cd004962.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management following closed reduction of traumatic anterior dislocation of the shoulder

Abstract: Conservative management following closed reduction of traumatic anterior dislocation of the shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…The concept of immobilization in ER was introduced by Itoi et al 25 in 2001, and since then multiple studies have been performed comparing different kinds of immobilization. In their Cochrane review, Braun and McRobert 6 concluded that the evidence was insufficient regarding whether immobilization in ER confers any benefit compared with immobilization in IR after FSD with regard to recurrent instability. The pooled recurrence rate was 22.4% for immobilization in ER versus 30% for immobilization in IR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The concept of immobilization in ER was introduced by Itoi et al 25 in 2001, and since then multiple studies have been performed comparing different kinds of immobilization. In their Cochrane review, Braun and McRobert 6 concluded that the evidence was insufficient regarding whether immobilization in ER confers any benefit compared with immobilization in IR after FSD with regard to recurrent instability. The pooled recurrence rate was 22.4% for immobilization in ER versus 30% for immobilization in IR.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled recurrence rate was 22.4% for immobilization in ER versus 30% for immobilization in IR. 6 None of the studies used an immobilization of 60° of ER plus 30° of ABD, which, according to biomechanical and arthroscopic data, is the best position for reduction of the labrum to allow healing in an anatomic position. 18 , 24 The degree of ER used varied from 0° to 30°, and in only 2 trials was the arm additionally immobilized in ABD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] Nevertheless, several articles reported a high incidence of poor functional outcome. [ 7 , 8 ] More and more studies have recommended that surgical procedure is an alternative choice for shoulder instability. [ 9 , 10 ] The rehabilitation after operation is a necessary condition for the recovery of shoulder joint activity.…”
Section: Introductionmentioning
confidence: 99%